The Influence of TikTok Social Media and Glow Up Trends on the Purchasing Interest of Cosmetic Products Among Residents of Boarding Houses in Padang Bulan - Simanungkalit, Betharia Agus Melli; Hasman, Haryaji Catur Putera; Salqaura, Siti Alhamra (Peneliti.net, 2023)
This research aims to examine the influence of social media and the glow-up trend on the purchasing interest of cosmetic products among boarders in Padang Bulan. The study employs a quantitative method with an associative approach. The population for this research consists of boarders in Padang Bulan, with a sample of 90 respondents. Data analysis is conducted using multiple linear regression tests. The results indicate that, partially, TikTok social media has a positive and significant effect on purchasing interest, and the glow-up trend has a positive and significant effect on purchasing interest. Simultaneously, TikTok social media and the glow-up trend have a positive and significant effect on purchasing interest. The coefficient of determination results show that the dependent variable of TikTok social media can be explained by the glow-up trend and purchasing interest by 17.3%, while the remaining 82.7% is influenced by other variables beyond the scope of this study.